Parental willingness of HPV vaccination in Mainland China: A meta-analysis - Sensen Tan; Sumeng Wang; Xunwen Zou; Xinhua Jia; Chenyunhao Tong; Jian Yin; Xuemei Lian; Youlin Qiao (Taylor & Francis Group, 2024)
ABSTRACTThis meta-analysis aimed to systematically review and analyze parental awareness of human papillomavirus (HPV) and its vaccine, as well as parental willingness of the HPV vaccine in China. The literature search selected studies that met the following criteria: study published between 2009 and 2023, study design involving parents with at least one child aged ≤ 18 years, sample sizes exceeding 300, availability of data on parental willingness of the HPV vaccine or sufficient information to calculate effect sizes, and studies published in either English or Chinese. Studies that did not meet one of the above points were excluded. From an initial pool of 660 papers, 33 studies were included, encompassing a total sample size of 92,802. The analysis revealed that the pooled awareness rates of HPV and the HPV vaccine among Chinese parents were 45.0% (95% CI: 36.1-54.0%) and 41.4% (95%CI: 30.7-52.5%), respectively. The overall parental willingness for vaccinating children against HPV was 61.0% (95% CI: 53.5-68.3%). Both parental awareness and willingness of the HPV vaccine in China were found to remain low when compared to other countries.